Experimental Study on the Aerodynamic Characteristics of Blades at the Last Stage of a Steam Turbine at Off-Design Conditions - Yunfeng Liu; Qiankun Jia; Xun Zhou; Hongtao Zhang; Yufeng Li; Zhongqi Wang; Wei Du (International Journal of Aerospace Engineering)
Experimental investigations have been carried out on the flow characteristics of the last stage long blades operating under off-design conditions. A model turbine test rig similar to a small power station was applied. The last stage blades with a scaling factor of 1 : 4.8 was used for pneumatic experiments. The rotor blade height was 375 mm, and the rotation speed was set to 7200 rpm. Five volumetric flow coefficients were utilized, corresponding to φ =0.61, 0.77, 0.92, 1.02, and 1.15. Pneumatic probes were used to focus on measuring pressures and swirl angles. The variation of different pneumatic parameters along the span and circumferential direction was investigated. The change patterns of the three-dimensional aerodynamic characteristics of the last stage blades during the off-design conditions were revealed. Results indicated that there was a high correlation between the variation of pneumatic parameters and different off-design conditions. In particular, the large meridional expansion angle at the tip led to abrupt changes in the inlet parameters, and the overlap even occupied by 17% blade height. Due to the influence of the exhaust hood, the circumferential static pressure-unevenness was up to 77.8% at the last stage outlet.